Communication And School Organization On Distance Learning - Rosvina Sari S; Joharis Lubis; Nathanael Sitanggang (International Journal of Educational Research & Social Sciences, 2021)
This study aims to find out how the conditions of communication and school organization at the time of distance learning are carried out, in terms of the individual scope, relationships between social groups and organizational groups, as well as emerging policies. distance learning, individual attitudes to school organizations, relationships between social groups, and policies. The results obtained in this study are that schools can continue to achieve educational goals with good quality with the integration between principals and teachers and all school resources, between organizations and policies must run according to the situation.